Evaluating the Protective Effects of MitoQ and Antifreeze Protein III on Cryopreserved Canine Sperm - Abbas Farshad; Emilia Diel; Axel Wehrend (Animals)
Cryopreservation can adversely affect sperm motility, structural integrity, and fertilization ability. This study investigated the effects of MitoQ and antifreeze protein III (AFP III) on frozen–thawed semen from eight adult dogs using a Tris–fructose extender. Ejaculates were divided and diluted with a standard Tris–fructose–egg yolk extender containing MitoQ (200 nM/mL) and AFP III (0.75, 1.0, 2.0 µg/mL), individually or combined. Post-thaw, samples were evaluated for motility, viability, membrane and acrosome integrity, lipid peroxidation, apoptosis indicators, mitochondrial function, and reactive oxygen species (ROS-H2O2). The results showed significant (p < 0.05) improvements in motility rate, progressive motility, VAP, VSL, VCL, ALH, and BCF with MitoQ or AFP alone. AFP III (0.75, 1.0 µg/mL) showed higher values than controls (p > 0.05), while MitoQ alone showed no significant effect. Viability and acrosome integrity improved with AFP III. Membrane integrity and lipid peroxidation were better in 0.75 and 1.0 µg/mL AFP III groups. ROS-H2O2 levels and mitochondrial membrane potential were unaffected except at 1.0 µg/mL AFP III. The phosphatidylserine translocation assay showed no significant differences in dead sperm between controls and individual treatments, but significant differences occurred with combined MitoQ/AFP III. In conclusion, AFP III and MitoQ in diluents protect canine sperm cells from cryodamage.